Динамика деформации объекта при магнитно-импульсной обработке материала с учетом пластических деформаций и температуры нагрева заготовки - Байда, Е.И. (Електротехніка і електромеханіка, 2011)
In the article, the dynamics of cylindrical tube deformation is considered under magnetic field action taking into account plastic strain and heating temperature of the workpiece.